PENERAPAN GRAMMAR TRANSLATION METHOD (GTM) DALAM MENINGKATKAN WRITING SKILL (WS) DAN SELF-DEVELOPMENT (SD) SISWA MADRASAH ALIYAH (MA) NW MENGKURU - Mul Muliadi (LPPM Institut Pendidikan Nusantara Global, 2022)
This study aimed at finding out the improving of writing skill (WS) and self-development (SD) students of MA by applying the Grammar Translation Method (GTM). This research is qualitative research. The research was conducted at Madrasah Aliyah (MA) NW Mengkuru, East Lombok, NTB. The data of this research collected through test and non-test. Based on the results of test and data analysis it can be concluded that the ability of students in improving writing skills using grammar translation method is very effective and needs to be applied and developed. The application of grammar translation method can improve students’ writing skills and self-development.